Aged care services in Australia and commentary on lessons learnt. Issue 1 (6th April 2018) - Chan, Daniel K. Y.; Chan, Luke K. M.
Abstract: The Australian aged care service is a mature and evolving service. It is comprehensive with good continuity of care between hospital and community. Innovative models of care that are built on the principles of improved efficiency, better quality, and safety are constantly being introduced as our population is aging, resulting in higher demand in our healthcare services and increasing healthcare cost. Collaborative effort of a multidisciplinary team underpins our successful aged care model as most of our older patients have multiple comorbidities with various functional and psychosocial needs. General practitioners play an important role in the care of older patients in the community.